I was recently watching blackpenredpen’s video (found here: https://m.youtube.com/watch?v=UJ3Ahpcvmf8) where he found the derivative of the the function $y = x^{x^x}$. Before watching the video, I decided to try it myself, and I didn’t it this way: Firstly I decided I would use the chain rule and define two functions, $u(x)$ and $v(x)$, both of which are $x^x$, so I could show the function as $u(v(x))$. Using the chain rule, the derivative would be: $u’(v(x))\cdot v’(x)$. We can find the derivative of $x^x$ (as shown on Quora here: https://www.quora.com/What-is-the-derivative-of-x-x-How-could-I-derive-it-as-well) as $x^x\cdot(\ln x+1)$. Now using the chain rule to get $u’(v(x))$ we get ${(x^x)}^{(x^x)}\cdot(\ln {x^x}+1)$ or $x^{x^{x+1}}\cdot(\ln {x^x}+1)$. This wasn’t the answer that blackpenredpen arrived at though. In the video, he arrived at $x^x\cdot x^{x^x}\left({\frac{1}{x}+\ln x+(\ln x)^2}\right)$. I can’t see how he did it, and I’m sure that it is right. If anyone could confirm my answer or show where I went wrong it would be greatly appreciated. Thanks.

  • 2
    note that $u(v(x))=v(x)^{v(x)}=(x^x)^{x^x}$, what is not the same function. Instead try the following: $x^{(x^x)}=\exp(x^x\ln x)=\exp(e^{x\ln x}\ln x)$, now use the chain rule. – Masacroso Nov 15 at 6:10
  • @Masacroso Are you sure? Exponentiation is left associative so $\alpha^{\alpha^\alpha}$ = $\alpha^{(\alpha^\alpha)}$. So wouldn’t ${(x^x)}^{x^x} = {(x^x)}^{(x^x)}$? – L. McDonald Nov 15 at 6:19
  • Yes, that is right. But the way I (tried) to find $\frac{d}{dx}\left[{x^{x^x}}\right]$ lead me to get a ${(x^x)}^{(x^x)}$ in my answer, this is probably where I’ve gone wrong. Note: this was in response to another comment, which seems to have been deleted. – L. McDonald Nov 15 at 6:28
up vote 2 down vote accepted

You can apply the method given on quora to your problem: $$\left(x^{x^x}\right)'=\left(e^{x^x\ln x}\right)'=e^{x^x\ln x}\cdot \left(x^x\ln x\right)'=\\ =e^{x^x\ln x}\cdot \left(e^{x\ln x}\ln x\right)'=\\ =e^{x^x\ln x}\cdot \left[\left(e^{x\ln x}\right)'\ln x+e^{x\ln x}\cdot \frac1x\right]=\\ =x^{x^x}\cdot \left[e^{x\ln x}\left(x\ln x\right)'\ln x+x^x\cdot \frac1x\right]=\\ =x^{x^x}\cdot \left[x^x\left(\ln x+1\right)\ln x+x^x\cdot \frac1x\right]=\\ =x^{x^x}\cdot x^x\left[\ln^2 x+\ln x+\frac1x\right].$$ P.S. I could not watch the referenced video on Youtube, because it is not opening here (it might be blocked).

  • Sorry about the video, he did almost exactly the same thing that you did, but might I ask, would you be able to show me where I went wrong? – L. McDonald Nov 15 at 7:49
  • If $u(x)=x^x, v(x)=x^x$, then $u(v(x))=(x^x)^{x^x}=x^{x^{x+1}}$, which is a different function. – farruhota Nov 15 at 7:54
  • Oh, I see, $u(v(x))$ would have been $x^{x^x}$ of course. That’s a bit embarrassing... – L. McDonald Nov 15 at 7:56

For differentiating expressions of the form $u(x)^{v(x)},$ I've always found it easiest to take logarithms and then differentiate implicitly. However, rather than work with the more general form $y = u^v,$ I'll work with $y = x^U$ (i.e. use $x$ for the base), which is sufficient to deal with $x^{x^x}.$

Taking the logarithm of both sides gives

$$ y = x^U \;\; \implies \ln y = \ln\left(x^U \right) \;\; \implies \;\; \ln y = U \cdot \ln x $$

Now differentiate both sides with respect to $x$:

$$ \frac{d}{dx}\left(\ln y\right) \;\; = \;\; \frac{d}{dx}\left(U \cdot \ln x \right) $$

$$ \frac{y'}{y} \;\; = \;\; \frac{d}{dx}(U) \cdot \ln x \; + \; U \cdot \frac{d}{dx} (\ln x) \;\; = \;\; U'\ln x \; + \; \frac{U}{x} $$

$$ y' \;\; = \;\; y \cdot \left[ U'\ln x \; + \; \frac{U}{x} \right] \;\; = \;\; x^U \cdot \left[ U'\ln x \; + \; \frac{U}{x} \right] $$

Using this result for $U(x) = x,$ we get

$$ \left(x^x\right)' \;\; = \;\; x^x \cdot \left[ 1 \cdot \ln x \; + \; \frac{x}{x} \right] \;\; = \;\; x^x(\ln x + 1) $$

Using that same result for $U(x) = x^x$ along with what we just found for $\left(x^x\right)',$ we get

$$ \left(x^{x^x}\right)' \;\; = \;\; x^{x^x} \cdot \left[ \left(x^x\right)' \cdot \ln x \; + \; \frac{x^x}{x} \right] $$

$$ \left(x^{x^x}\right)' \;\; = \;\; x^{x^x} \cdot \left[ x^x(\ln x + 1) \cdot \ln x \; + \; \frac{x^x}{x} \right] $$

$$ \left(x^{x^x}\right)' \;\; = \;\; x^{x^x} \cdot x^x \cdot \left[ (\ln x + 1)\ln x \; + \; \frac{1}{x} \right] $$

$$ \left(x^{x^x}\right)' \;\; = \;\; x^{x^x} \cdot x^x \cdot \left[ (\ln x)^2 \; + \; \ln x \; + \; \frac{1}{x} \right] $$

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.